The prevalence and correlates of undiagnosed HIV among Australian gay and bisexual men: results of a national, community‐based, bio‐behavioural survey. Issue 1 (11th November 2015) - Holt, Martin; Lea, Toby; Asselin, Jason; Hellard, Margaret; Prestage, Garrett; Wilson, David; de Wit, John; Stoové, Mark
Abstract : Introduction: Gay and bisexual men (GBM) with undiagnosed HIV are believed to contribute disproportionately to HIV transmission in Australia but national prevalence estimates have been lacking. Methods: From November 2013 to November 2014, we recruited men at gay venues and events in six Australian states and territories. Of 7291 survey participants, 3071 men also provided an oral fluid sample for testing and decided whether to receive their test results or not. We calculated raw and population‐weighted prevalence estimates and identified associations with undiagnosed infection using logistic regression. Results: Of 3071 participants, 213 men tested HIV‐positive (6.9%, 95% confidence interval [CI] 6.0 to 7.8%), of whom 19 (8.9%, 95% CI 5.8 to 13.5%) were previously undiagnosed. After weighting for the size of the gay and bisexual male population in each state or territory, national HIV prevalence was estimated to be 7.2% (95% CI 6.3 to 8.1), of which 9.1% (95% CI 6.0 to 13.6%) were estimated to be undiagnosed. Compared with HIV‐negative participants, men with undiagnosed HIV were more likely to report meeting partners at sex venues, using antiretroviral drugs as pre‐exposure prophylaxis, condomless anal intercourse with casual partners, using party drugs for sex, injecting drugs and using amyl nitrite, crystal methamphetamine or gamma hydroxybutyrate in the six months prior to the survey. Discussion: The results indicate that the prevalence of undiagnosed HIV is relatively low among Australian GBM but is higher among men who report riskier sex and drug practices. Conclusions: The results underline the importance of targeted HIV prevention and frequent testing for men at increased risk of infection.